A conceptual model of vegetation dynamics for the unique obligate‐seeder eucalypt woodlands of south‐western Australia. (23rd April 2018) - Gosper, Carl R.; Yates, Colin J.; Cook, Garry D.; Harvey, Judith M.; Liedloff, Adam C.; McCaw, W. Lachlan; Thiele, Kevin R.; Prober, Suzanne M.
Abstract: Models of vegetation dynamics framed as testable hypotheses provide powerful tools for predicting vegetation change in response to contemporary disturbances or climate change. Synthesizing existing information and applying new data, we develop a conceptual model of vegetation states and transitions for the previously overlooked woodlands dominated by obligate‐seeder eucalypts of dry to semi‐arid south‐western Australia. These comprise the largest extant temperate woodland globally, are uniquely dominated by a high diversity of obligate‐seeder eucalypts (55 taxa), but are under threat from wildfire. Our conceptual model incorporates four critical ecological processes that also distinguish obligate‐seeder woodlands from temperate woodlands dominated by resprouting eucalypts: (i) a lack of well‐protected epicormic buds results in major disturbances (prominently fire) being stand‐replacing. The pre‐disturbance tree cohort is killed, followed by dense post‐disturbance recruitment from seed shed from a serotinous seed bank; (ii) competition between saplings leads to self‐thinning over a multi‐century timeframe, with surviving individuals having great longevity (regularly >400 years); (iii) multiple processes limit recruitment in the absence of stand‐replacement disturbances, leading to frequent single‐cohort stands. However, unlike the few other obligate‐seeder eucalypt communities, trickle recruitment in very long‐unburnt stands can facilitate indefinite community persistence in the absence of stand‐replacement disturbances; and (iv) discontinuous fuels, relatively low understorey flammability (low grass and often high chenopod cover) and topographic barriers to fire (salt lakes) allow mature woodlands to persist for centuries without burning. Notably though, evidence suggests that flammability peaks at intermediate times since fire, establishing a 'flammability bottleneck' (or landscape fire trap) through which regenerating woodlands must pass. Our model provides a framework to support management to conserve obligate‐seeder eucalypt woodlands. Research into reasons for exceptional tree heights relative to ecosystem productivity, the evolution of diverse and dominant obligate‐seeder eucalypts, the paucity of grass, and the recent spatial distribution of fires, will further inform conservation management.